Pengaruh Ketebalan Membran Terhadap Sifat-Sifat Membran (Contact Angle, Porositas dan Selektivitas) - Winandri, Kautsar Rahman; Anjuda, Adli Putra; Santi, Sintha Soraya (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Polymeric membranes are commonly used materials for gas separation. Blending polymers with inorganic fillers is the most efficient way to improve membrane performance. Fillers used to date include zeolite, silica, metal organic framework (MOF) and carbon molecular sieve (CMS). However, in practice, the fillers used in membrane production are considered to be expensive. Biochar is a carbon-rich solid material produced by the combustion of organic materials or biomass with little or no oxygen (pyrolysis). Biochar is also readily available and its cost is relatively affordable. Biochar has similarities to CMS in that both contain carbon, with the commercial biochar used in this study being 70% carbon. The thickness of a membrane can affect the selectivity value of the membrane due to differences in filtration thickness. The membranes made with biochar fillers and different membrane thicknesses were then tested to determine their properties. Based on the tests conducted, it was found that the membranes produced had a higher density as the membrane thickness increased. In addition, the membranes produced were also hydrophilic. The highest selectivity value was achieved by the membrane with a thickness of 500 µm.